Intracellular labeling method for chip-based capillary electrophoresis fluorimetric single cell analysis using liposomes - Sun, Yue; Lu, Min; Yin, Xue-Feng; Gong, Xing-Guo (Journal of Chromatography A, 2006)
An intracellular derivatization method mediated by liposome was developed for single cell analysis with chip-based capillary electrophoresis (CE) and laser-induced fluorescence (LIF) detection. Liposomes with an average diameter of 100 nm were produced from phosphatidylcholine to encapsulate fluorescent dyes by an ultrasonic method. The encapsulation yield and the vesicle density were determined to be 46 ± 5% and 8.8 × 10 14/mL, respectively. The amount of fluorescent dye that entered the cells was dependent on the duration of incubating cells with liposomes, liposome density, and concentration of the dye solution encapsulated in liposomes. The described method introduced cell membrane nonpermeable fluorescent dyes into living cells without reducing cell viability. Single cell analysis using microfluidic chip-based CE revealed that liposome-membrane fusion occurred after entrance of liposomes into the cells, with release of encapsulated fluorescence dyes and labeling of intracellular species.